Pengaruh Discount dan Fear of Missing Out (FOMO) terhadap Keputusan Pembelian Produk Fashion pada Aplikasi TikTok di Kota Gorontalo - Asrul Hidayatullah Alimuddin; Tineke Wolok; Djoko Lesmana Radji (Transbahasa, 2026)
This study aims to examine the influence of discounts and Fear of Missing Out (FOMO) on consumers' purchasing decisions for fashion products on the TikTok application in Gorontalo City. The rapid growth of social commerce through TikTok has transformed consumer behavior, making purchasing decisions increasingly influenced by both economic incentives and psychological factors. This research employed a quantitative approach using primary data collected through questionnaires distributed to TikTok users who had previously purchased fashion products through the platform. The sample size was determined using the Lemeshow formula, and respondents were selected through a purposive sampling technique, resulting in a total of 96 participants. Data were analyzed using multiple linear regression analysis to assess the individual and simultaneous effects of the independent variables on purchasing decisions. The findings reveal that discounts have a positive and significant effect on purchasing decisions, indicating that price reductions encourage consumers to make purchases. Fear of Missing Out (FOMO) was also found to have a positive and significant influence, suggesting that consumers tend to purchase products due to concerns about missing trends, promotions, or opportunities available on TikTok. Furthermore, discounts and FOMO simultaneously exert a significant influence on purchasing decisions. These findings indicate that consumer purchasing behavior is shaped not only by rational economic considerations but also by emotional and social motivations in the digital marketplace.